Gas Leakage Detection Using Thermal Imaging Technique - M. S., Jadin; Kamarul Hawari, Ghazali (2014)
Gas leakage is one of the hazards that can cause major incidents to human injuries, fires as well as high impact on economic. To avoid such situation, a preventive inspection is paramount important. Since gas leakage is unseen by naked eyes due to the energy that are emitted by gas are too small to simulate by eyes, thermal imaging technology is used to detect and evaluate the severity level of the leakage. This paper presents a method for detecting gas leak using infrared image analysis. Through an image filtering technique, the target region of interests is enhanced and segmented to extract the leaky regions. The image feature is extracted to identify the leakage. From the experimental result, it shows that this system is effective in detecting the presence of gas leakage in real industrial problem.